Overexpression of Bovine FcRn in Mice Enhances T-Dependent Immune Responses by Amplifying T Helper Cell Frequency and Germinal Center Enlargement in the Spleen - Schneider, Zita; Jani, Péter Károly; Szikora, Bence; Végh, Attila; Kövesdi, Dorottya; Iliás, Attila; Cervenak, Judit; Balogh, Péter; Kurucz, István; Kacskovics, Imre (Frontiers in Immunology, 2015)
The neonatal Fc receptor (FcRn) plays key roles in IgG and albumin homeostasis, maternal IgG transport, and antigen presentation of IgG-opsonized antigens. Previously, we reported that transgenic (Tg) mice that overexpress the bovine FcRn (bFcRn) have augmented T-dependent humoral immune response with increased IgG protection, higher level of antigen-specific antibodies, greater number of antigen-specific B cells, and effective immune response even against weakly immunogenic epitopes. In the current study, we analyzed the localization of the bFcRn in secondary lymphoid organs, and focused to demonstrate the in vivo impact of its overexpression in the spleen on the course of antibody production. bFcRn was highly expressed by red pulp macrophages and marginal zone macrophages in the spleen and by subcapsular sinus macrophages and macrophage-like cells in the interfollicular areas in the lymph node cortex. We also demonstrated that splenic dendritic cells of Tg mice express bFcRn and intraperitoneal immunization of these mice with T-dependent antigens led to more than threefold increase in the number of antigen-specific activated T helper cells with increased size and numbers of germinal centers compared to wild-type controls. bFcRn expression in splenic B cells was also detected and that may also contribute to the enhanced B cell activation. Finally, we demonstrated that these Tg mice developed efficient immune response against very low dose of antigen, reflecting another important practical benefit of these Tg mice.